(NdOROGA WETROW(B: [(NpUTEWYE ZAMETKI(B] / s (N~ASTX (B2s - (NeFREMOW(B, (NiWANs ((NmOSKWA(B: s (NmOLODAQ GWARDIQ(B, s, 1986)
(NwO WTOROJ TOM sOBRANIQ SO^INENIJ i(B. (Na(B. (NeFREMOWA WO[LA KNIGA (B"(NdOROGA wETROW (B((NgOBIJSKIE ZAMETKI(B)".s
rus
Keywords: (NpRIKL@^ENIQ(B, (NPUTE[ESTWIQs; (NnAU^NAQ FANTASTIKAs; (NzAMETKIs